2021
DOI: 10.1073/pnas.2024583118
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the protochromic green/red photocycle of the chromatic acclimation sensor RcaE

Abstract: Cyanobacteriochromes (CBCRs) are bilin-binding photosensors of the phytochrome superfamily that show remarkable spectral diversity. The green/red CBCR subfamily is important for regulating chromatic acclimation of photosynthetic antenna in cyanobacteria and is applied for optogenetic control of gene expression in synthetic biology. It is suggested that the absorption change of this subfamily is caused by the bilin C15-Z/C15-E photoisomerization and a subsequent change in the bilin protonation state. However, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 67 publications
3
39
0
Order By: Relevance
“… 3 , 4 The phytochrome family uses a lineage of the GAF domain that binds a thioether-linked tetrapyrrole chromophore for light sensing. 5 8 Phytochromes play an essential role in light-regulated processes, e.g., phototaxis, pigmentation, and photosynthesis, and are interesting also as targets for optogenetic applications, imaging in tissues, light-dependent gene expression, and possible medical applications. 9 14 BphP in the Deinococcus radiodurans cells, in addition to its responsibility for pigmentation and growth, is potentially involved in the resistance of these bacteria to ionizing radiation and mutagenic factors by participating in the DNA damage response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 The phytochrome family uses a lineage of the GAF domain that binds a thioether-linked tetrapyrrole chromophore for light sensing. 5 8 Phytochromes play an essential role in light-regulated processes, e.g., phototaxis, pigmentation, and photosynthesis, and are interesting also as targets for optogenetic applications, imaging in tissues, light-dependent gene expression, and possible medical applications. 9 14 BphP in the Deinococcus radiodurans cells, in addition to its responsibility for pigmentation and growth, is potentially involved in the resistance of these bacteria to ionizing radiation and mutagenic factors by participating in the DNA damage response.…”
Section: Introductionmentioning
confidence: 99%
“…At the atomistic level, a series of conformational changes in light-responsive proteins, referred to as the protein photocycle, is triggered by absorbing the energy of a photon. One example of complexes in which photoisomerization can induce a large conformational change in the protein environment is the phytochrome family which represents a diverse class of photoreceptors present in plants, and fungal and bacterial kingdoms. , The phytochrome family uses a lineage of the GAF domain that binds a thioether-linked tetrapyrrole chromophore for light sensing. Phytochromes play an essential role in light-regulated processes, e.g., phototaxis, pigmentation, and photosynthesis, and are interesting also as targets for optogenetic applications, imaging in tissues, light-dependent gene expression, and possible medical applications. BphP in the Deinococcus radiodurans cells, in addition to its responsibility for pigmentation and growth, is potentially involved in the resistance of these bacteria to ionizing radiation and mutagenic factors by participating in the DNA damage response …”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteriochromes (CBCRs) are phytochrome-related photosensor proteins that are confined but widespread within the cyanobacteria phylum . CBCRs utilize the Z / E photoisomerization of the bilin as phytochromes but combine additional chemical reactions to create their spectral diversity covering all visible, near-UV, and far-red regions of the spectrum. The green/red-type CBCR, which includes RcaE and CcaS, is one of the most important subfamilies due to their physiological roles for regulating photosynthetic antenna in cyanobacteria. This subfamily photoconverts between a green-absorbing C15 -Z ( 15 Z Pg) dark state and red-absorbing C15 -E ( 15 E Pr) photoproduct. A pH-titration experiment suggested that their phycocyanobilin (PCB) chromophore is deprotonated in 15 Z Pg and protonated in 15 E Pr, and this was later proven by a 15 N NMR experiment . Namely, this subfamily utilizes a change of the bilin protonation state to cause a green/red absorption shift, which is designated “protochromic photocycle” …”
Section: Introductionmentioning
confidence: 99%
“…None of the CA4 regulatory genes have thus far been shown to negatively interact with other regulatory genes (for example those responsible for photosynthesis or nutrient acquisition) though such interactions have not been tested explicitly. Sensory mechanisms for detecting light color in marine CA4 Synechococcus strains have not yet been identified, but signal transduction pathways for light sensing in other plastic cyanobacteria strains can be energy intensive and could serve as a cost to CA4 strains (Grossman and Kehoe, 1997;Terauchi et al, 2004;Gutu et al, 2013;Kehoe, 2016, 2019;Nagae et al, 2021). Limitations associated with matching the external environment to acclimaters' phenotypes are also possible (Stomp et al, 2008), especially since some CA4 strains undergo lag times before initiation of acclimation to green light (Everroad et al, 2006;Humily et al, 2013).…”
Section: Introductionmentioning
confidence: 99%